Level of Knowledge about Developmental Language Disorder among Primary School Teachers in Lima-Peru and Madrid-Spain - Dioses Chocano, Alejandro S. (2025)
Developmental Language Disorder (DLD), formerly known as Specific Language Impairment (SLI), is a severe disorder with a prevalence of approximately 7% in the child population, that impact on oral and written communication, however, it is little known by clinicians and teachers, which prevents it from being detected and pedagogical responses given at the beginning of schooling. For this reason, we sought to describe and compare the knowledge of Primary School teachers about SLI/DLD in five aspects: definition, characteristics, causes, intervention and epidemiology. To this end, 107 teachers in Lima and Madrid completed a Sociodemographic Data Sheet and the Specific Language Impairment Knowledge Questionnaire. The results show statistically significant differences between the groups, with Spanish teachers performing better in the aspects of definition, characteristics, causes and epidemiology. This group also reported higher university education (94%) and more training in language disorders (86%), in contrast to the Peruvian teachers (53%; 45,3%), who were more likely to err in their answers. Although there were no differences in the overall level of knowledge or intervention, the findings highlighted the need to strengthen SLI/DLD education in academic settings by including initial pedagogical responses to reduce these training gaps and direct them towards more specialized and premeditated support.